2014
DOI: 10.1111/eea.12237
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour and biology ofChilo partelluson maize landraces

Abstract: Plants defend themselves against herbivores through activation of both constitutive and induced defences. Previous studies reported that egg deposition on maize landraces induces the release of volatiles that attract parasitoids, but little is known on the effect of these volatiles on subsequent herbivore oviposition. In addition, larval preference and development on these maize landraces is unknown. We evaluated six landraces and one hybrid maize variety for their resistance to Chilo partellus (Swinhoe) (Lepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
1
10
1
Order By: Relevance
“…moth oviposition (Mutyambai et al, 2014(Mutyambai et al, , 2015 or through the attraction of natural enemies (Khan et al, 1997;Tamiru et al, 2011;Mutyambai et al, 2015). In our study, however, no statistically significant difference was detected in the moth oviposition between maize plants grown in soil from push-pull and non-push-pull fields.…”
Section: Soil-mediated Emergent Properties Of Companion Croppingcontrasting
confidence: 82%
See 1 more Smart Citation
“…moth oviposition (Mutyambai et al, 2014(Mutyambai et al, , 2015 or through the attraction of natural enemies (Khan et al, 1997;Tamiru et al, 2011;Mutyambai et al, 2015). In our study, however, no statistically significant difference was detected in the moth oviposition between maize plants grown in soil from push-pull and non-push-pull fields.…”
Section: Soil-mediated Emergent Properties Of Companion Croppingcontrasting
confidence: 82%
“…While this could be attributed to limited sample size, this result could also be an indication for two biological phenomena at play. First, in previous studies herbivore-or oviposition-induced VOC emissions had been found as factors driving oviposition choices of C. partellus adults (Mutyambai et al, 2014(Mutyambai et al, , 2015. The VOC emissions induced by push-pull soil may include some of the same compounds but as a bouquet may not contain the same information for the female moths as herbivore-induced VOCs.…”
Section: Soil-mediated Emergent Properties Of Companion Croppingmentioning
confidence: 99%
“…The larva of C. partellus is the damaging stage which makes tunnels into maize leaves, tassels and stems causing yield loss of up to 80% and therefore threatens food security (Kfir et al 2002;Khan et al 2007Khan et al , 2010. Chilo partellus has also been reported to cause damage on other crops such as sorghum, sugar cane, forage crops and wild grasses (Harris 1990;Khan et al 1997;Mutyambai et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, plants respond to herbivore attack through production of a number of chemical signals known as herbivore-induce plant volatiles (HIPVs), which have direct and/or indirect effects on the attacking herbivore. Directly, these chemical cues negatively affect the physiology or behaviour of the herbivore, either as toxins, digestibility reducers or deterrents [ 6 , 7 ]. Indirectly, plants use these HIPVs to attract natural enemies of the herbivores, as well as increase the foraging success of these natural enemies, thereby facilitating improved control of herbivores [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%